IMPLEMENTASI ALGORITMA FORWARD CHAINRING DAN CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSA EFEK SAMPING BAHAN PEMUTIH KOSMETIK PADA KULIT - Ardiansyah, Rizka; Indrajaya, Muhammad Aristo; Joefrie, Yuri Yudhaswana; Pratiwi, Inten Sakti (Foristek, 2023)
Most people, especially women, are generally not educated about what ingredients are contained in a cosmetic and only rely on social media as a reference by looking at influencers who advertise a beauty product. To consult with a dermatologist also requires a lot of money, so they choose not to care about it, this causes many cases handled by dermatologists are cases that are too severe. Therefore, there is a need for awareness and education for women, especially teenagers regarding the use of illegal cosmetics, so through this research, the authors try to propose a free, expert-based platform that can be accessed in general by people from anywhere and anytime to carry out self- assessments or self-examinations. or education that makes it easier for the public to get easy and detailed information access regarding the hazardous ingredients contained in cosmetics. So in this study, we propose an educational media and expert-based assessment of the symptoms of the disease suffered in the form of developing an expert system based on the forward chaining algorithm and certainty factor, which involves a dermatologist. based on the results of testing the accuracy of 20 data samples, 18 data were appropriate and 2 data were not appropriate so that the accuracy obtained was 90%, and from user satisfaction testing it was found that 80% were satisfied with the system created and 20% were not satisfied.